2019
DOI: 10.26794/2587-5671-2019-23-2-17-30
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Trade Credit Dynamics During Crisis: Panel Data Analysis for Macedonian Firms

Abstract: The study is aimed at determining the factors influencing the trade credits dynamics for twenty three firms registered on the Macedonian Stock Exchange, as well as at checking for crisis effects from 2011 to 2015. The study includes a review of the literature on commercial credit factors; elaborately analyzed descriptive statistics of the collected data and dependent variable variance; tests for unobservable effects and their functional form; evaluation of panel regression and interpretation of the results. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The results of the evaluated panel regression model for companies engaged in the production and processing of milk in the Republic of Serbia established the existence of a statistically significant and positive influence of liquidity on the profitability of the observed companies. Based on the regression coefficient, it can be determined that with an increase in liquidity, an increase in profitability can be expected, which is in line with the results obtained by Dakić et al [19] during the analysis of dairy companies, as well as by Deari and Lakshina [50]. A positive and statistically significant impact, based on the estimated regression model, was also found in the turnover ratio of total business assets, i.e., it was confirmed that more efficient management of total business assets leads to higher profitability of the observed companies.…”
Section: Dairy Processorssupporting
confidence: 87%
“…The results of the evaluated panel regression model for companies engaged in the production and processing of milk in the Republic of Serbia established the existence of a statistically significant and positive influence of liquidity on the profitability of the observed companies. Based on the regression coefficient, it can be determined that with an increase in liquidity, an increase in profitability can be expected, which is in line with the results obtained by Dakić et al [19] during the analysis of dairy companies, as well as by Deari and Lakshina [50]. A positive and statistically significant impact, based on the estimated regression model, was also found in the turnover ratio of total business assets, i.e., it was confirmed that more efficient management of total business assets leads to higher profitability of the observed companies.…”
Section: Dairy Processorssupporting
confidence: 87%
“…The variable CCC2 is the squared CCC, and it is included to investigate whether the relationship between firm profitability and CCC follows some nonlinear mechanism. To our best knowledge, from a methodological point of view, the inclusion of the CCC2 variable represents the main innovation compared to the previous evidence in the case of North Macedonia (see e.g., Deari et al, 2019;Deari, 2015). For example, Naumoski (2019) also examined 720 firms in ten South-Eastern European countries in the period 2006-2015 using a panel regression model.…”
Section: Descriptive Statisticsmentioning
confidence: 99%